Chemicals for life and living - Ochiai, Ei-ichiro 1936- (Springer, 2011)
Chemicals often have a negative Image among the general public. But there is no material world or indeed human beings without chemicals. The material world is operated by chemicals. The title 'Chemicals for Life and Living' implies that the material world is staged and played by chemicals.